Construction of performance indicators for recreational spaces: a resource to measure accessibility and social interaction (REVISTA NODO, 2023)
In accordance with the right that citizens have to the recreation exercise in coexistence with public spaces, whether natural or created, this work exposes, within the framework of the categories of accessibility and social interaction, a group of indicators to facilitate the measurement, with greater precision and homogeneity, of the performance of the function for which said sites were created. For the determination of the variables and the calculation factors of the indicators, interpretative and coding procedures were used that allowed the construction of a resource that is effective for diagnosing the diversity of recreation scenarios in the environment of the cities. The category of controlled accesses and walkways, which includes three indicators, and the category of amenities and attractions, which includes two more, are disaggregated. The proposal is complemented with two additional factors that respond to the status that the infrastructure must present for surveillance and to have the information of interest.
Keywords: Public Space